ANALYSIS OF THE DAMAGE TO THE ENVIRONMENT OF THE LITHIUM-ION BATTERY AS A COMMON TYPE OF BATTERY FOR MODERN ELECTRIC VEHICLES - Solarov, Oleksandr; Klieshch, Oleh; Zarva, Maksym; Palyvoda, Yehor (Collection of scientific papers «ΛΌГOΣ», 2023)
As far back as the 1970s of the 20th century, there were attempts to invent rechargeable lithium electric batteries, but they were unsuccessful due to the violent reactions of lithium with water, which made it impossible to provide the required level of safety for the relatively safe operation of this type of battery. The first lithium-ion battery was first introduced to the market in 1991.